Novecento Cubano : La naturaleza el hombre los dioses : Pintura cubana del 900. - Museo Nacional de Cuba, La Habana; Alonso, Alejandro G.; Culturali, Giacimenti; Fernandez, Pilar (La Habana : Edizioni Chronodata, 1995)
Lam, Wifredo ; Abela, Eduardo ; Enriquez, Carlos ; Garcia, Victor Manuel ; Ponce, Fidelio ; Arche, Jorge ; Pogolotti, Marcelo ; Pelaez, Amelia ; Rodriguez, Mariano ; Portocarrero, René ; Pedro, Luis Martinez ; Carreno, Mario ; Puig, Ernesto Gonzalez ; Martinez, Raúl ; Eiriz, Antonia ; Leon, Angel Acosta ; Sosabravo, Alfredo ; Moreno, Servando Cabrera ; Lopez, Minerva ; Mendive, Manuel ; Fonseca, Ever ; Fong, Flora ; Dominguez, Nelson ; Oliva, Pedro Pablo ; Sanchez, Tomas ; Garciandia, Flavio ; Bedia, José ; Finale, Moises
biografie
Novecento Cubano : La naturaleza el hombre los dioses, Museo Nacional de Cuba, La Habana, 1995
Italiaans
Spaans
boek